1989
DOI: 10.1104/pp.89.1.260
|View full text |Cite
|
Sign up to set email alerts
|

Glucosinolate Uptake by Developing Rapeseed Embryos

Abstract: Embryos excised from the seed of rapeseed (Brassica napus L.) accumulated glucosinolate from the culture medium. Uptake was saturable, subject to inhibition, varied with the developmental stage of the embryo but correlated with the time of accumulation of glucosinolates In situ. It is suggested that a carrier-mediated transport system is operating in the developing embryo.During embryogenesis, glucosinolates accumulate in the seed of rapeseed (Brassica napus L). At maturity, the embryo comprises from 80 to 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
3
19
1
Order By: Relevance
“…The biosynthesis of seed glucosinolates could involve the transport of glucosinolate biosynthetic enzymes, the RNA encoding those enzymes, or glucosinolates themselves, from the maternal tissues to the embryo. Consistent with the latter hypothesis are recent physiological studies that have suggested that embryos of B. napus developing in vitro acquire their glucosinolates from the exogenous medium rather than synthesizing them de novo (5,7).…”
Section: Time (Minutes)supporting
confidence: 63%
See 2 more Smart Citations
“…The biosynthesis of seed glucosinolates could involve the transport of glucosinolate biosynthetic enzymes, the RNA encoding those enzymes, or glucosinolates themselves, from the maternal tissues to the embryo. Consistent with the latter hypothesis are recent physiological studies that have suggested that embryos of B. napus developing in vitro acquire their glucosinolates from the exogenous medium rather than synthesizing them de novo (5,7).…”
Section: Time (Minutes)supporting
confidence: 63%
“…The effect of the gsml-l allele on shoot growth was tested as follows. Flats were planted with alternating rows of wild-type and TU1 plants and kept at 4°C for 7 . Glucosinolates in TUl shoots after feeding various compounds.…”
Section: Growth Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, however little was known about the influence of exogenous glucosinolates on plant morphology. A report by Gijzen et al (1989) found that the addition of 2-propenylglucosinolate to a growth medium containing rapeseed embryos resulted in a decline in embryo fr. wt.…”
Section: Comparison Of Symptomsmentioning
confidence: 99%
“…Similarly glucosinolates are synthesized in leaves and translocated to seeds during development in Tropaeolus majus (Lykkesfeldt & Moller 1993). A carrier mediated system has been proposed for accumulation of glucosinolates in developing rapeseed embryos (Chen & Halkier 2000, Gijzen et al 1989. To investigate if similar pattern of transport and accumulation occurs in soybean seed isoflavonoids, the ability of soybean embryos to synthesize isoflavonoids were assessed and maternal effect on seed isoflavonoids was determined (Dhaubhadel et al 2003).…”
Section: Regulation Of Isoflavonoid Biosynthesis In Soybean Seedsmentioning
confidence: 99%